2009
DOI: 10.1002/iub.243
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐1 activity of plasma membrane affects HT20 colon cancer cell migration

Abstract: SummaryRecent studies revealed an important role of aquaporins (AQPs) in cell migration and migration-associated cell function such as angiogenesis, wound healing, and neutrophil motility. Migration of tumor cells is a crucial step in tumor invasion and metastasis. In the present study, we investigated the expression of AQP1 in human HT20 colon cancer cells and characterized its function in cell migration. By reverse transcription-polymerase chain reaction (RT-PCR) and immunoblot analysis, expression of AQP1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 21 publications
5
61
0
Order By: Relevance
“…Recently, various studies have focused on the association of AQPs and cancer (10)(11)(12)(13)(14)(15)(16)(17). AQP1 is expressed in vascular endothelial cells throughout the body, except in the normal central nervous, genital and lymphoid systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, various studies have focused on the association of AQPs and cancer (10)(11)(12)(13)(14)(15)(16)(17). AQP1 is expressed in vascular endothelial cells throughout the body, except in the normal central nervous, genital and lymphoid systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Moon et al (10) reported that AQP1 was associated with colorectal carcinogenesis and Yiang (12) reported that the AQP1 activity in plasma membranes affected HT20 colon cancer cell migration in vitro. Those findings revealed that the expression of AQP1 is associated with tumor progression in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenovirus vector was a common virus vector in gene therapy (Benlahrech et al, 2009;Jiang, 2009). It had many advantages, such as strong infection ability, high titer, efficient multicopy, no insertional mutagenesis, no genetic toxicity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism for AQP1-enhanced motility remains unknown, both ion and water channels are essential in the cellular migration process (Schwab et al, 2007). AQP1 expression has been linked to metastasis and invasiveness of colon cancer cells (Jiang, 2009;Yoshida et al, 2013). In mammary and melanoma cancer cells, AQP1 facilitates tumor cell migration in vitro and metastasis in vivo (Hu and Verkman, 2006).…”
Section: Introductionmentioning
confidence: 99%